2021
DOI: 10.1186/s40779-021-00339-y
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of olfactory and taste disorders among COVID-19 patients in China

Abstract: To determine the prevalence and clinical features of olfactory and taste disorders among coronavirus disease 2019 (COVID-19) patients in China. A cross-sectional study was performed in Wuhan from April 3, 2020 to April 15, 2020. A total of 187 patients with confirmed severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) completed face-to-face interviews or telephone follow-ups. We found that the prevalence of olfactory and taste disorders was significantly lower in the Chinese cohort than in foreign COV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
2
0
2
Order By: Relevance
“…In a cross-sectional study in China involving 187 patients with confirmed severe COVID-19 infection, it is purported that the SARS-CoV-2 virus neuroinvades via olfactory sensory neurons, colonising olfactory bulb tissue. Increased expression of ACE2 in the nasopharynx may lead to an increased risk of olfactory and taste symptoms [35]. The authors also propose using olfactory or taste disturbance as an early-warning symptom to screen for patients potentially infected with COVID-19, especially in the absence of rhinitis.…”
Section: Effect On Organ Systemsmentioning
confidence: 99%
“…In a cross-sectional study in China involving 187 patients with confirmed severe COVID-19 infection, it is purported that the SARS-CoV-2 virus neuroinvades via olfactory sensory neurons, colonising olfactory bulb tissue. Increased expression of ACE2 in the nasopharynx may lead to an increased risk of olfactory and taste symptoms [35]. The authors also propose using olfactory or taste disturbance as an early-warning symptom to screen for patients potentially infected with COVID-19, especially in the absence of rhinitis.…”
Section: Effect On Organ Systemsmentioning
confidence: 99%
“…24 Pada kalangan perempuan, gangguan penghidu secara signifikan lebih umum dibandingkan dengan laki-laki karena adanya gen ACE-2 yang terletak pada kromosom X dan memiliki tingkat ACE-2 yang lebih tinggi sehingga perempuan lebih mungkin terinfeksi COVID-19 dibandingkan laki-laki. 25 Hal ini didukung dengan adanya penelitian yang dilakukan di Harlan Laboratories, Indianapolis, yang menyatakan bahwa terdapat perbedaan aktivitas ACE dengan tingkat Angiotensin (1-7) terhadap jenis kelamin. Pada penelitian tersebut, korteks ginjal tikus normotensif pada betina memiliki aktivitas ACE yang lebih besar dan tingkat Angiotensin (1-7) daripada jantan.…”
Section: Jenis Kelaminunclassified
“…26 Selain itu, adanya pengaruh hormonal yang mengakibatkan indera penghidu perempuan lebih jelas berfluktuasi dan lebih sensitif dibandingkan laki-laki. 25…”
Section: Jenis Kelaminunclassified
“…Among the most common symptoms of COVID-19 is taste dysfunction, which has a ranging clinical presentation 1 , 2 ]. Although its pathophysiology remains to be unclear [ 3 , 4 ], indirect damage to taste receptors by the viral infection of epithelial cells of the tongue and subsequent local inflammation seems to be the key factor [5] . Likewise, several treatments are proposed for COVID-19-related taste dysfunction; however, there is not enough information about efficacy and safety [3] .…”
Section: Introductionmentioning
confidence: 99%